2005
DOI: 10.1007/s00417-004-1088-3
|View full text |Cite
|
Sign up to set email alerts
|

Progression of visual field defects and visual loss in trabeculectomized eyes

Abstract: Progression of VF defects and development of visual impairment due to glaucoma was fairly common despite trabeculectomy. Both were associated with severity of initial VF defect. In this series, no significant correlation appeared between defect progression and the last IOP, but association between stability of VF and the amount of IOP reduction after surgery indicate that a lower target IOP level particularly in eyes with initially severe VF defect would, however, be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In trabeculectomy without antiproliferative agents, Parc et al reported that 47% of eyes had gone blind after 10 years;18 others found a VF worsening in 41%19 and 46% of eyes;20 and in a large series (700 trabeculectomies), long-term success (IOP<21 mm Hg, no worsening of the visual field and no loss of visual acuity) was found in 44.4% 21…”
Section: Discussionmentioning
confidence: 98%
“…In trabeculectomy without antiproliferative agents, Parc et al reported that 47% of eyes had gone blind after 10 years;18 others found a VF worsening in 41%19 and 46% of eyes;20 and in a large series (700 trabeculectomies), long-term success (IOP<21 mm Hg, no worsening of the visual field and no loss of visual acuity) was found in 44.4% 21…”
Section: Discussionmentioning
confidence: 98%
“…[2,3] Nevertheless, a considerable proportion of patients with POAG have visual impairment, even when the IOP is significantly decreased following glaucoma surgery. [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that lowering intraocular pressure (IOP) slowed the advancement of visual field damage in glaucoma patients. [1][2][3][4][5][6][7][8][9] However, even if the IOP can be substantially lowered, the reduction of mean and peak IOPs does not always prevent visual field progression. [10][11][12] There are several reports that diurnal IOP variation is a risk factor for glaucoma.…”
Section: Introductionmentioning
confidence: 99%